Design of Vacuum Post‐Drying Procedures for Electrodes of Lithium‐Ion Batteries. Issue 9 (30th June 2021) - Huttner, Fabienne; Marth, Axel; Eser, Jochen C.; Heckmann, Thilo; Mohacsi, Jonas; Mayer, Julian K.; Scharfer, Philip; Schabel, Wilhelm; Kwade, Arno
Abstract: In order to reduce the residual moisture in lithium‐ion batteries, electrodes and separators need to be post‐dried prior to cell assembly. On an industrial scale, this is often conducted batch‐wise in vacuum ovens for larger electrode and separator coils. Especially for electrodes, the corresponding post‐drying parameters have to be carefully chosen to sufficiently reduce the moisture without damaging the sensitive microstructure. This requires a fundamental understanding of structural limitations as well as heat transfer and water mass transport in coils. The aim of this study is to establish a general understanding of the vacuum post‐drying process of coils. Moreover, the targeted design of efficient, well‐adjusted and application‐oriented vacuum post‐drying procedures for electrode coils on the basis of modelling is employed, while keeping the post‐drying intensity as low as possible, in order to maintain the sensitive microstructure and to save time and costs. In this way, a comparatively short and moderate 2‐phase vacuum post‐drying procedure is successfully designed and practically applied. The results show that the designed procedure is able to significantly reduce the residual moisture of anode and cathode coils, even with greater electrode lengths and coating widths, without deteriorating the sensitive microstructure of the electrodes. Abstract : Vacuum post‐drying : To reduce residual moisture in lithium‐ion batteries, cell components need to be post‐dried before cell assembly. Based on previous experimental findings, research and theoretical estimations of heat and mass transfer, an efficient, well‐adjusted vacuum post‐drying procedure for electrode coils is successfully designed and practically applied in this study.